2018
DOI: 10.1177/2041731418810164
|View full text |Cite
|
Sign up to set email alerts
|

Equine lung decellularization: a potential approach for in vitro modeling the role of the extracellular matrix in asthma

Abstract: Contrary to conventional research animals, horses naturally develop asthma, a disease in which the extracellular matrix of the lung plays a significant role. Hence, the horse lung extracellular matrix appears to be an ideal candidate model for in vitro studying the mechanisms and potential treatments for asthma. However, so far, such model to study cell–extracellular matrix interactions in asthma has not been developed. The aim of this study was to establish a protocol for equine lung decellularization that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
1
12
0
1
Order By: Relevance
“…This preferential colonization likely involved complex cellular mechanisms including integrin expression, adhesion, migration and proliferation and suggests that the decellularized tissue retained enough of its native qualities to allow this process to occur. Da Palma et al demonstrated that the fibroblasts recellularizing a decellularized horse lung are expressing the N-cadherin, an adhesion biomarker (da Palma, et al, 2018). This protein may play an important role in the ASM cell migration seen in our study as it has been shown that the migration of the vascular smooth muscle cells is slowed down by the inhibition or the down-regulation of the Ncadherin (Lyon, et al, 2010, Wang, et al, 2018.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This preferential colonization likely involved complex cellular mechanisms including integrin expression, adhesion, migration and proliferation and suggests that the decellularized tissue retained enough of its native qualities to allow this process to occur. Da Palma et al demonstrated that the fibroblasts recellularizing a decellularized horse lung are expressing the N-cadherin, an adhesion biomarker (da Palma, et al, 2018). This protein may play an important role in the ASM cell migration seen in our study as it has been shown that the migration of the vascular smooth muscle cells is slowed down by the inhibition or the down-regulation of the Ncadherin (Lyon, et al, 2010, Wang, et al, 2018.…”
Section: Discussionsupporting
confidence: 59%
“…Indeed, previous studies have recellularized respiratory tissues mainly with stem cells (Crabbe, et al, 2015, Doi, et al, 2017. Recent studies have recellularized horse lung tissues with equine dermal fibroblasts and canine yolk sac cells (da Palma, et al, 2018), and mouse lungs with human and murine fibroblasts (Burgstaller, et al, 2018). McClure et al grafted a decellularized skeletal muscle in the gastrocnemius and demonstrated a regeneration of the graft with the presence of cells and neuromuscular junctions (McClure, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since decellularised tissues possess the native ECM components and structure, they could be of great value in applications that require 3D ex vivo platforms, such as disease modelling to study their progression and new targets, as well as screening and investigation of drugs/ therapeutics. 75,76,94 Such application can be very relevant in cancer, where the biological activity of cancerous cells is not only affected by physicochemical changes in the ECM, but also they can alter the ECM by, for example, applying mechanical forces for expansion or by secreting enzymes that promote cancer spread. A tumour comprises a microenvironment that undergoes remodelling following extracellular, intercellular and intracellular signals.…”
Section: Use Of Decellularised Scaffolds As 3d Ex Vivo Platformsmentioning
confidence: 99%
“…Regarding neutrophilic asthma, inhaled insulin-like growth factor binding protein-3 peptide was reported as novel therapeutic target for severe non-T2 asthma through the modulation of endoplasmic reticulum stress in the lung [8]. Furthermore, as horses naturally develop asthma, unlike conventional research animals, an equine asthma model consisting of decellularised lung scaffolds [9] was proposed as a platform for the study of cell-extracellular matrix interactions and remodelling in asthma [10].…”
Section: Mechanisms and Physiologymentioning
confidence: 99%